LEGAL PRAGMATISM AS AN ARGUMENTATIVE METHOD OF JUSTIFICATION OF THE DECISION MAKING BY THE APPLICATOR OF THE GENERAL ANTIELISIVE STANDARD (Reflection and Critique Law Magazine, 2022)
This article aims to use the methodology of legal pragmatism in justifying decision making by the applicator of the anti-elision rule, contained in the paragraph of article 116 of the National Tax Code, especially after the introduction of article 20 in the Law of Introduction to the Rules of Brazilian Law. For this purpose, a bibliographic research was conducted in order to undertake a relationship between the legal-philosophical method proposed by Pragmatism and the meaning and scope of art. 20 of the LINDB and art. 116 from CTN.